Monomethyl auristatin E Exhibits Potent Cytotoxic Activity against Human Cancer Cell Lines SKBR3 and HEK293 - Abdollahpour-Alitappeh, Meghdad; Razavi-vakhshourpour, Sepand; Lotfinia, Majid; Jahandideh, Saeed; Najminejad, Hamid; Balalaie, Saeed; Moazzami, Reza; Shams, Elnaz; Habibi-Anbouhi, Mahdi; Abolhassani, Mohsen (Novelty in Biomedicine, 2017)
Background: Monomethyl auristatin E (MMAE) is a synthetic analog of dolastatin 10, a compound originally isolated from the marine mollusk. MMAE, as a highly potent microtubule inhibitor, exerts its potent cytotoxic effect by inhibiting microtubule assembly, tubulin-dependent GTP hydrolysis and microtubes polymerization. This molecule, by itself, lacks the tumor specificity required to elicit therapeutic benefit. Nevertheless, the extremely cytotoxic potential of MMAE could be harnessed in the form of MMAE-antibody conjugates. The aim of the present study was to evaluate the cytotoxic activity of MMAE against breast (SKBR3) and kidney (HEK293) cancer cell lines in an in vitro cell-based assay. Materials and Methods: SKBR3 and HEK293 cells were treated with different concentrations ranging from 0.002048, 0.01024, 0.0512, 0.256, 1.28, 6.4, 32, 160, 800 and 4000 nM of MMAE, and cell viability was determined after 72 hours using an MTT colorimetric assay. The effect of MMAE was regularly monitored by direct observation using an invert microscope. Results: Microscopic observation showed that there was a concentration-dependent increase in cell death. Results from the MTT assay revealed a statistically significant loss of viability (P<0.0001) at concentrations ranging from 0.01024 to 4000 nM in SKBR3 cells, and 0.0512 to 4000 nM in HEK293 cells. Our findings showed that MMAE inhibited the growth of SKBR3 and HEK293 cells in a concentration-dependent manner, with IC50 values of 3.27 ± 0.42 and 4.24 ± 0.37 nM, respectively. Conclusion: MMAE was able to significantly inhibit cell growth at nanomolar concentrations, emphasizing its great potential for the development of antibody-drug conjugates.